Harmony within Diversity: The Internalization of Religious Moderation as a Pillar in Sustaining National Identity - Khalilurrahman, Khalilurrahman; Sugiono, Sugiono; Manshur, Umar; Munif, Muhammad (JURNAL ISLAM NUSANTARA, 2023)
This research analyses Religious Moderation in maintaining national identity in Madrash Aliyah Ihyaul Islam Pajarakan Probolinggo. The research uses a qualitative case study type approach. Data collection techniques were carried out through participant observation, in-depth interviews and documentation. Meanwhile, the data analysis uses Miles and Huberman's descriptive analysis: data reduction, data presentation, and conclusion. The results of this research show that the internalization of religious moderation in maintaining national identity in Madrash Aliyah Ihyaul Islam is carried out through the integration of moderate values in the madrasa curriculum, the integration of moderate values in learning activities, the integration of moderate values through the role of educators and education staff, design students with Pancasila character and exemplary role models. The internalization of religious moderation in maintaining national identity is expected to shape the character of students who are humanist, religious, tolerant, plural, moderate, nationalist, democratic and patriot.